Expression of p53, Ki-67 and c-erb B2 in growth hormone-and/or prolactin-secreting pituitary adenomas Expressão de p53, Ki-67 e c-erb B2 em adenomas hipofisários secretores de prolactina e/ou hormônio de crescimento - Carlos Henrique A. Botelho; Albino Verçosa de Magalhães; Paulo Andrade de Mello; Fernando C. Schmitt; Luiz Augusto Casulari (Arquivos de Neuro-Psiquiatria)
The subcellular events implicated on the formation and behavior of pituitary adenomas are not fully understood. In this study we investigated the presence of p53, Ki-67 and c-erb B2 in 38 pituitary adenomas with immunohistochemical positivity for GH and prolactin (n=26; 68.4%), for prolactin (n=9; 23.7%) and for GH (n=3. 7.8%). The analyses revealed the following results: 24 (63.2%) tumors expressed variable positivity for c-erb B2, 11 (28.9%) expressed p53 positivity and 11 (28.9%) tumors were variably positive for Ki-67. Our results demonstrated a high percentage of GH/prolactin-, prolactin- and GH-secreting tumors with immunohistochemical positivity for c-erb B2. Once this membrane receptor is related to growth factors EGF and TGFalpha and both have a definite effect on tumor growth, our data suggest a possible role for c-erb B2 on the evolution of these tumors. Os eventos subcelulares implicados na formação e comportamento dos adenomas hipofisários não são completamente compreendidos. Neste estudo nós investigamos a presença de p53, Ki-67 e c-erb B2 em 38 adenomas hipofisários com positividade imuno-histoquímica para GH e prolactina (n=26, 68,4%), para prolactina (n=9, 23,7%) e para GH (n=3, 7,8%). A análise revelou os seguintes resultados: 24 tumores (63,2%) expressaram positividade variável para c-erb B2, 11 (28,9%) expressaram positividade para p53 e 11 tumores (28,9%) foram variavelmente positivos para Ki-67. Nossos resultados demonstraram elevada percentagem de tumores secretores de GH/prolactina, prolactina e GH com positividade imuno-histoquímica para c-erb B2. Desde que este receptor de membrana está relacionado aos fatores de crescimento EGF e TGFalfa e ambos têm efeito definido no crescimento tumoral, nossos dados sugerem possível função para o c-erb B2 na evolução destes tumores.